System design and control for waste heat recovery of automotive engines based on Organic Rankine Cycle. (1st May 2016) - Shi, Rongqi; He, Tianqi; Peng, Jie; Zhang, Yangjun; Zhuge, Weilin
Abstract: In this study, a novel and practical design for an ORC (Organic Rankine Cycle) system is presented. It can be applied to waste heat recovery of unsteady heat sources, such as exhaust gas of automobile engines. According to the variation characteristics of exhaust gas temperature and mass flow rate, the EGMR (Exhaust Gas Mixture Recirculation) loop is designed. The exhaust gas flowing out of the evaporator is partially recovered and mixed with the real-time engine exhaust gas, and then led to recirculation in the evaporator. Moreover, an energy storage module is also introduced, which is simplified as a metal block with internal tubes. A control approach based on ADRC (Active Disturbance Rejection Control is established. It is composed of an outer sub-loop controller for the evaporating pressure, a control allocator for mass flow rate allocation of the exhaust gas, and an inner sub-loop controller for the valve openings. The system is evaluated according to the numerical simulations. The results show that it can work steadily and reliably. The control error of the evaporating pressure is lower than 0.1%, and the fluctuation of the superheating is less than 1 °C. Compared with the conventional ORC system, both the cycle and the overall energy efficiencies are increased significantly. Furthermore, since no extra thermodynamic cycle or working fluid is demanded, the system architecture is more practical and simpler than most previous designs of system improvement. Highlights: The Exhaust Gas Mixture Recirculation design is proposed for unsteady heat source. The ORC system works steadily based on Active Disturbance Rejection Control. The efficiencies of the EGMR system are higher than those of the conventional one. The system architecture is simple and practical without extra thermodynamic cycle.